Environmental factors in epithelial barrier dysfunction - Celebi Sözener, Zeynep; Cevhertas, Lacin; Nadeau, Kari; Akdis, Mübeccel; Akdis, Cezmi A. (Journal of allergy and clinical immunology, 2020)
The main interfaces controlling and attempting to homeostatically balance communications between the host and the environment are the epithelial barriers of the skin, gastrointestinal system, and airways. The epithelial barrier constitutes the first line of physical, chemical, and immunologic defenses and provides a protective wall against environmental factors. Following the industrial revolution in the 19th century, urbanization and socioeconomic development have led to an increase in energy consumption, and waste discharge, leading to increased exposure to air pollution and chemical hazards. Particularly after the 1960s, biological and chemical insults from the surrounding environment—the exposome—have been disrupting the physical integrity of the barrier by degrading the intercellular barrier proteins at tight and adherens junctions, triggering epithelial alarmin cytokine responses such as IL-25, IL-33, and thymic stromal lymphopoietin, and increasing the epithelial barrier permeability. A typical type 2 immune response develops in affected organs in asthma, rhinitis, chronic rhinosinusitis, eosinophilic esophagitis, food allergy, and atopic dermatitis. The aim of this article was to discuss the effects of environmental factors such as protease enzymes of allergens, detergents, tobacco, ozone, particulate matter, diesel exhaust, nanoparticles, and microplastic on the integrity of the epithelial barriers in the context of epithelial barrier hypothesis.